The Use of Loora as Media to Check Grammar in Speaking for Undergraduated Students - Dandi Salmanda; Ernita Daulay (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study examines the effectiveness of Loora, an artificial intelligence (AI)-based language learning application, in improving English speaking skills and grammatical accuracy among university students. Using a qualitative case study approach involving 10 participants, this study explores how Loora provides real-time and personalized feedback that encourages independent, reflective, and active language use in line with Swain's Output Hypothesis. The results indicate that Loora significantly improves students' confidence, awareness of grammatical errors, and speaking habits by providing detailed explanations and instant corrections. Despite limitations such as a small sample size and infrastructure challenges, the findings suggest that AI-based tools like Loora can effectively support language learning by making feedback more accessible and engaging. This study highlights the potential of integrating innovative technological solutions into language education to enhance learning autonomy, grammatical accuracy, and overall speaking ability.